2019
DOI: 10.1016/j.cell.2019.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Chromatin by Intrinsic and Regulated Phase Separation

Abstract: Highlights d Chromatin undergoes liquid-liquid phase separation (LLPS) under physiologic conditions d Linker DNA length and patterning, histone H1, and acetylation modulate chromatin LLPS d Acetylated chromatin only phase separates upon binding multi-bromodomain proteins d LLPS could enable establishment and maintenance of distinct chromatin compartments

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
913
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 823 publications
(971 citation statements)
references
References 91 publications
53
913
5
Order By: Relevance
“…Recent models have proposed that the low-affinity interactions that drive phase condensation may be sufficient for both enhancer-promoter colocalization as well as promoting transcriptional activation 3,67 . Computational simulation has suggested that formation of these structures may promote long-range chromatin interactions 3 , and BRD4 is capable of driving clustering of acetylated chromatin in vitro 68 . In support of this, BRD4 intrinsically disordered regions (IDRs) targeted to telomeric sequences appear to bring loci together 35 and dissolution of phase condensate structures prevents the estrogen-induced colocalization of enhancers 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent models have proposed that the low-affinity interactions that drive phase condensation may be sufficient for both enhancer-promoter colocalization as well as promoting transcriptional activation 3,67 . Computational simulation has suggested that formation of these structures may promote long-range chromatin interactions 3 , and BRD4 is capable of driving clustering of acetylated chromatin in vitro 68 . In support of this, BRD4 intrinsically disordered regions (IDRs) targeted to telomeric sequences appear to bring loci together 35 and dissolution of phase condensate structures prevents the estrogen-induced colocalization of enhancers 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Examples include cytoplasmic processing bodies (P bodies) associated with RNA metabolism (Decker and Parker, 2012); promyelocytic leukemia nuclear bodies (PML NBs) involved in transcription, DNA damage repair, and anti-viral responses (Lallemand-Breitenbach and de Thé, 2010); signaling clusters in T cell activation (Su et al, 2016); and HP1 clusters in heterochromatin organization (Larson et al, 2017;Strom et al, 2017). Many condensates form through self-assembly of multivalent molecules, including proteins composed of folded domains and/or disordered regions, RNA and DNA, and chromatin (Li et al, 2012;Kato et al, 2012;Nott et al,2015;Su et al, 2016;Banani et al, 2017;Gibson et al, 2019). This process can lead to both liquid-like and solid-like structures (Banani et al, 2017;Shin and Brangwynne, 2017;Alberti and Dormann, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin itself can be described as a molecular condensate generated by histone tail-driven phase separation, whereby acetylation of histones promotes transition to a distinct phaseseparated chromatin state (Gibson et al, 2019). Chromatin itself can be described as a molecular condensate generated by histone tail-driven phase separation, whereby acetylation of histones promotes transition to a distinct phaseseparated chromatin state (Gibson et al, 2019).…”
Section: Ofmentioning
confidence: 99%
“…Liquid-liquid phase separation underlies the formation of stress-induced membraneless compartments such as cytosolic stress granules and nSBs. Chromatin itself can be described as a molecular condensate generated by histone tail-driven phase separation, whereby acetylation of histones promotes transition to a distinct phaseseparated chromatin state (Gibson et al, 2019). Interestingly, phosphorylation of RNA polymerase II (POL2) at its IDR (the C-terminal domain) appears to dictate whether POL2-in its hypophosphorylated form-preferentially associates with condensates that mediate transcription initiation or-in its hyperphosphorylated form -associates with condensates characterized by a high concentration of splicing factors (Guo et al, 2019).…”
mentioning
confidence: 99%